HUBUNGAN ANTARA HARGA DIRI DENGAN PREFERENSI PEMILIHAN PASANGAN HIDUP - Salahudin Liputo; Moh. Wahyu Madina (program studi psikologi, 2023)
This study aims to determine the level of self-esteem, the level of preference for choosing a life partner, and to find out the relationship between self-esteem and preferences for choosing a life partner in nursing students, Faculty of Health Sciences, Universitas Muhammadiyah Gorontalo, class of 2018. The design of this research is correlation qualitative. The sample was taken by accidental sampling technique with a sample of 59 respondents. Data analysis in this study used Product Moment Pearson technique. The results of this study indicate that: (1) The level of self-esteem of students is in the high category with a large percentage of 61%, (2) The level of preference for choosing a life partner of students is in the medium category with a percentage of 96.6%, (3) Based on the results of the analysis conducted, found the correlation coefficient r = 0.540 with p = 0.000 (0.000p <0.05). These results indicate if Ha is accepted, which means that self-esteem (X) is related to the preference for choosing a life partner (Y).